ANALISIS FAKTOR DEMOGRAFI, AKSES MEDIA DAN SUMBER INFORMASI TERHADAP KEPEDULIAN DAN KESADARAN LINGKUNGAN KONSUMEN: KAJIAN PEMASARAN YANG BERWAWASAN SOSIAL - M.F. Shellyana Junaedi (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2003)
This study attempts to offer more insights into the dynamic nature of ecologicallyconscious consumer behavior. It also provides profiling and segmenting food purchase decisionmakers (mostly females) based upon ecologically-conscious consumer behavior. The data suggests that demographic criteria, media consumption, and green product source of information significantly influence the ecologically-conscious consumer behavior. It also provides some implications to marketers operating in organic-product market.Keywords: demographic, media consumption, source of information, ecologically conscious, organic